2014
DOI: 10.4081/mr.2014.5511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low power microwave radiation on pigment production in bacteria

Abstract: Effect of low power (90 W) microwave (MW) radiation (2450 MHz) on bacterial growth and pigment production was studied in three different bacteria. Microwave exposure of 2-6 min duration was able to alter growth and pigment production (prodigiosin production by Serratia marcescens, violacein production by Chormobacterium violaceum, and staphyloxanthin production by Staphylococcus aureus) in the test organisms significantly. In this study, pigment production was estimated in the cell population originated from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Further, many of their effects may be reversible, for example a sonic stimulated culture may revert back to the normal behavior, soon after removal of the external acoustic field. Reversible nature of MW-induced mutations has previously been indicated by us (Raval et al, 2014). Though underdeveloped at present, further systematic research in this area may pave the way for development of novel therapeutic applications.…”
Section: Effect Of Mw Treatment On Bacterial Virulencementioning
confidence: 81%
“…Further, many of their effects may be reversible, for example a sonic stimulated culture may revert back to the normal behavior, soon after removal of the external acoustic field. Reversible nature of MW-induced mutations has previously been indicated by us (Raval et al, 2014). Though underdeveloped at present, further systematic research in this area may pave the way for development of novel therapeutic applications.…”
Section: Effect Of Mw Treatment On Bacterial Virulencementioning
confidence: 81%
“…Reports demonstrated reversible nature of microwave effect in over producing mutants of Xanthomonas campestris, were shown to revert back to the parent phenotype and in low dose microwave induced effects in Drosophila melanogaster which disappeared after few generations. The reversion of mutation was due to restoration of microbial repair system to its efficiency after few subcultures [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Using RF-EMFs to alter the growth of various fungi and bacteria have been studied before. However, these studies showed different results based on species and intervention traits [ 11 - 13 ]. In this light, Kushwah et al ., reported while 2 min exposure to 2450 MHz MW radiation enhanced Streptococcus mutans growth, four minutes of the same exposure reduced the growth of Pectobacteriumcarotovorum [ 7 ].…”
Section: Discussionmentioning
confidence: 99%